Bioreduction of Precious Metals by Microorganism: Efficient Gold@N‐Doped Carbon Electrocatalysts for the Hydrogen Evolution Reaction. Issue 29 (24th May 2016) - Zhou, Weijia; Xiong, Tanli; Shi, Chaohong; Zhou, Jian; Zhou, Kai; Zhu, Nengwu; Li, Ligui; Tang, Zhenghua; Chen, Shaowei
Abstract: The uptake of precious metals from electronic waste is of environmental significance and potential commercial value. A facile bioreductive synthesis is described for Au nanoparticles (ca. 20 nm) supported on N‐doped carbon (Au@NC), which was derived from Au/ Pycnoporus sanguineus cells. The interface and charge transport between Au and N‐doped carbon were confirmed by HRTEM and XPS. Au@NC was employed as an electrocatalyst for the hydrogen evolution reaction (HER), exhibiting a small onset potential of −54.1 mV (vs. RHE), a Tafel slope of 76.8 mV dec −1, as well as robust stability in acidic medium. Au@NC is a multifunctional electrocatalyst, which demonstrates high catalytic activity in the oxygen reduction reaction (ORR), as evidenced by an onset potential of +0.97 V, excellent tolerance toward methanol, and long‐term stability. This work exemplifies dual recovery of precious Au and fabrication of multifunctional electrocatalysts in an environmentally benign and application‐oriented manner. Abstract : Rags to riches : Gold nanoparticles supported on N‐doped carbon (Au@NC) derived from the bioreduction of gold ions by Pycnoporus sanguineus cells are active HER electrocatalysts with a small onset potential of −54.1 mV and a Tafel slope of 76.8 mV dec −1 . The catalyst is a stable and eco‐friendly candidate for energy applications. Key: a) bioreduction by Au@microorganism, b) calcination, c) catalysis.